1997
DOI: 10.1038/ki.1997.106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early and late antihypertensive treatment on extracellular matrix proteins and mononuclear cells in uninephrectomized SHR

Abstract: The efficacy of an early and late treatment with the angiotensin converting enzyme inhibitor lisinopril or the angiotensin II receptor blocker ICI D8731 was investigated in uninephrectomized spontaneously hypertensive rats (SHR). Rats that underwent uninephrectomy (UNX) at six weeks of age were randomly assigned to receive no treatment, lisinopril shortly after UNX, lisinopril starting 16 weeks after UNX, ICI D8731 shortly after UNX, and ICI D8731 starting 16 weeks after UNX. Blood pressure was normalized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…3). Similar increments in helper T cells were found by Geiger et al [30]although their study is not strictly comparable to ours because their protocol included uninephrectomy that would add the proinflammatory effects of renal mass reduction.…”
Section: Discussionsupporting
confidence: 82%
“…3). Similar increments in helper T cells were found by Geiger et al [30]although their study is not strictly comparable to ours because their protocol included uninephrectomy that would add the proinflammatory effects of renal mass reduction.…”
Section: Discussionsupporting
confidence: 82%
“…We have identified the AT 1 R as a significant molecular imaging target because of its intricate involvement in the many aspects of renal physiology and pathology, [17][18][19] particularly in acute, subacute, and chronic complications of renal ischemia. 20,21 The AT 1 R is a key injury response protein because its continuing activation leads to stimulation of the extracellular matrix, 22 collagen deposition, glomerular remodeling, 23 inflammation, 24 apoptosis, 25 generation of oxygen species, and cell cycle arrest. 26 To this end, our group has synthesized several radioligands and tested them in various animal models for positronemission tomography (PET) imaging of the renal AT 1 R. [27][28][29][30][31] One particular radioligand, [ 11 C]KR31173, has shown excellent image quality in multiple animal species including nonhuman primates.…”
mentioning
confidence: 99%
“…Losartan is a AT1 receptor antagonist and it inhibited the synergistic effect of Ang II, thus demonstrating that this effect is a specific effect. In vivo , the administration of ACE inhibitors and Ang II receptor antagonists to animal models of glomerulosclerosis and interstitial fibrosis have been reported to ameliorate and foreshorten the disease process 4,25,26 . In vitro , it was shown that selective antagonism of the AT1 receptor inhibits Ang II‐stimulated DNA and protein synthesis in various kinds of cultured cells 8,9,14,24 .…”
Section: Discussionmentioning
confidence: 99%